Single vs. multiple operators for chronic total occlusion percutaneous coronary interventions: From the PROGRESS‐CTO Registry. Issue 3 (25th January 2023) - Karacsonyi, Judit; Alaswad, Khaldoon; Krestyaninov, Oleg; Karmpaliotis, Dimitri; Kirtane, Ajay; Ali, Ziad; McEntegart, Margaret; Masoumi, Amirali; Poomipanit, Paul; Jaffer, Farouc A.; Khatri, Jaikirshan; Choi, James; et al.
Abstract: Background: There is limited data on the impact of a second attending operator on chronic total occlusion (CTO) percutaneous coronary intervention (PCI) outcomes. Methods: We analyzed the association between multiple operators (MOs) (>1 attending operator) and procedural outcomes of 9296 CTO PCIs performed between 2012 and 2021 at 37 centers. Results: CTO PCI was performed by a single operator (SO) in 85% of the cases and by MOs in 15%. Mean patient age was 64.4 ± 10 years and 81% were men. SO cases were more complex with higher Japan‐CTO (2.38 ± 1.29 vs. 2.28 ± 1.20, p = 0.005) and Prospective Global Registry for the Study of Chronic Total Occlusion Intervention scores (1.13 ± 1.01 vs. 0.97 ± 0.93, p < 0.001) compared with MO cases. Procedural time (131 [87, 181] vs. 112 [72, 167] min, p < 0.001), fluoroscopy time (49 [31, 76] vs. 42 [25, 68] min, p < 0.001), air kerma radiation dose (2.32 vs. 2.10, p < 0.001), and contrast volume (230 vs. 210, p < 0.001) were higher in MO cases. Cases performed by MOs and SO had similar technical (86% vs. 86%, p = 0.9) and procedural success rates (84% vs. 85%, p = 0.7), as well as major adverse complication event rates (MACE 2.17% vs. 2.42%, p = 0.6). On multivariable analyses, MOs were not associated with higher technical success or lower MACE rates. Conclusion: In a contemporary, multicenter registry, 15% of CTO PCI cases were performed by multiple operators. Despite being more complex, SO cases had lower procedural and fluoroscopy times, and similar technical and procedural success and risk of complications compared with MO cases.